Spontaneous collapse of syringomyelia - Vásquez, Víctor; Tello, Carlos; Piantoni, Lucas; Remondino, Rodrigo; Galaretto, Eduardo; Noel, Mariano (Revista Argentina de Neurocirugía, 2025)
Background: the association between Chiari malformation type I (CM), scoliosis and syringomyelia is well known; spontaneous collapse of the syringomyelia cavity is not, which is highly infrequent. Objectives: to report a case of spontaneous collapse of syringomyelia and to analyze the bibliography on the subject. Case description: a 4-and-a-half-year-old patient was diagnosed with Chiari malformation type I associated with syringomyelia and scoliosis. The evolution of the syringomyelia cavity and scoliosis was monitored by magnetic resonance imaging (MRI) and spinograms. Surgery: during the observation, spontaneous resolution of the syringomyelia was evident. Regarding the CM, surgical treatment was decided to control the scoliosis, which progressed despite decompression and was resolved by instrumented arthrodesis. Conclusion: our case provides information to the literature for understanding the possible natural evolution of syringomyelia.